Determination of free fatty acids in crude vegetable oil samples obtained by high-pressure processes - Carolina Medeiros Vicentini-Polette (Elsevier, 2021)
This study determined the total acidity, fatty acids profile (TFAs), and free fatty acids (FFAs) present in sunflower and soybean oils obtained by green processes (supercritical carbon dioxide-scCO2 and pressurized liquid extraction-PLE). The determination of the primary fatty acids responsible for product acidity can provide a higher quality product. Sunflower (scCO2/PLE-ethanol) and soybean (PLE-ethanol/PLE-hexane) samples were evaluated. The TFAs profile was determined by gas chromatography - mass spectrometry. The total FFAs content was determined by titrimetric method. For the qualitative determination of the FFAs present in the oils, a new technique capable of repeatably identifying the main FFAs was applied, using GC/MS. The primary fatty acids (palmitic, stearic, oleic, linoleic, eicosenoic, and linolenic) were present in all samples, both as TFAs and FFAs. However, fatty acids of lesser intensity showed variations. The applied methodology provided relevant data on the FAs that cause acidity in vegetable oils obtained by green processes.